PEMBELAJARAN STATISTIKA TERKAIT UKURAN PEMUSATAN DATA (MEAN, MODUS, DAN MEDIAN) MELALUI INTEGRASI TERHADAP AL-QUR’AN - Liny Mardhiyatirrahmah (Sekolah Tinggi Agama Islam (STAI) Al-Wahliyah Barabai, 2023)
Statistics consists of how to plan, collect, analyze, then interpret, and finally display data. Although studied at various school levels, statistics is still taught in general, without being linked to the Qur’an, especially in Islamic-based schools or tertiary institutions. Therefore, the integration between religious sciences and general science, especially statistics, is very much needed in schools. Learning statistics related to the size of the concentration of data, namely the mean, median, and mode, can be integrated with the Qur'an. This can be seen from the existence of examples that can be taken using the number of verses, names of surahs, and other prayer services that can be related to this. This integration between statistics and the Qur’an can indirectly help eliminate the assumption that the Koran and general science cannot be collaborated. This research is focused on developing a learning process with a scientific approach that can help understanding statistics related to the size of data concentration. The research method used in this study is the research and development method, which includes the use of descriptive methods, action research, and experiments. The results prove that this integration is a bright spot to be able to combine the two sciences when teaching in class to get more meaningful learning. Students can also become more aware of what the Qur'an contains by frequently interacting through this integration.